ANALISIS POLA ASUH OTORITER TERHADAP KEMAMPUAN SOSIAL EMOSIONAL ANAK USIA 4 - 5 TAHUN DI PPT MUTIARA BUNDA: Indonesia - Cholilah, Cholilah; Wahono, Wahono; Kurniawati, Tri; Sa’ida, Naili (Jurnal Manajemen Pendidikan, 2025)
This study aims to identify the parenting style applied by parents and its influence on the social- emotional development of children aged 4–5 years at PPT Mutiara Bunda, Wonokusumo Village, Semampir District, Surabaya City, in the 2024–2025 academic year. This research uses a qualitative approach with a case study method. The subjects of this study consisted of three students along with their parents who applied an authoritarian parenting style. Data were collected through observation, interviews, and documentation, using a triangulation approach to validate the data from various sources. The data analysis technique refers to the Miles and Huberman model, which includes three main stages: (1) data reduction, which involves sorting, summarizing, and focusing raw data into relevant categories such as social- emotional indicators; (2) data display in the form of observation tables and field notes to illustrate children's behavior in aspects such as empathy, cooperation, and emotional control; and (3) conclusion drawing/verification based on consistent patterns found in the field. The results of the study show that the parenting style applied at PPT Mutiara Bunda is authoritarian, characterized by strict rules and control without allowing children to express their opinions. Children raised in an authoritarian environment tend to exhibit hindered social- emotional development, such as fearfulness, low self-confidence, lack of initiative, poor decision-making skills, and social withdrawal.